Numeryczna analiza stateczności skarp podczas wykonywania wykopu w gruntach zaburzonych glacitektonicznie = Numerical analysis of slope stability during excavation in glacitectonically deformed soils - Szajna, Waldemar St. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an application of the finile element method for slope stability analysis as an alternative to traditional methods of limit equilibrium. An elasto-plastic constitutive model of soil is taken into account. Slope failure produced by finite element approach occurs naturally in the zones where shear stresses exceeds shear strength of the soil.
Keywords: X jubileuszowe sympozjum glacitektoniki